DESAIN TATAKELOLA SISTEM INFORMASI MANAJEMEN BERBASIS WEBSITE PADA MADRASAH ALIYAN NURUL ULUM MENGGUNAKAN ENTEPRISE ARCHITECTURE PLANNING (EAP) - Saputra, Andika; Warisno, Andi; Murtafiah, Nurul Hidayati (STIT AL MULTAZAM, 2022)
The design of this academic information system aims to make it easier for students, teachers and schools who previously knew quite a long time of information, here I make it easier for students, teachers and schools with an academic information system (online), so that it can be efficient and effective. This journal aims to build an online academic information system. The design system for creating an academic website at MA Nurul Ulum was developed using some Apache Web Server software, PHP and MySQL. The tables used in making the academic web at this school are student tables, teacher tables, grades tables, schedule tables, login tables, attendance tables. All of these tables will later be used to accommodate the data needed in the development of an academic website at MA Nurul Ulum. In this study, the Enterprise Architecture Planning methodology is used, which is the process of defining the architecture in the use of information to support the business and plans to implement the architecture. The architecture itself consists of data architecture, application architecture and technology architecture. Architecture here is like a blueprint and a drawing or model. The blueprint resulting from the Enterprise Architecture Planning process will be used as a guide for making blueprints in strategic planning for Management Information Systems and information technology as a whole at MA Nurul Ulum. The use of SWOT analysis to create a system according to the needs for administrative management of Nulul Ulum MA, a school information system that can be used as a means of promotion as well as an academic information system.